L’infezione razziale: cure e palliativi (Altre Modernità, 2011)
L’infezione razziale: cure e palliativiNino Verri, Lume Lume.(Palermo, Sellerio Editore, 2010, pp.132. ISBN 88-389-2460-0)Riccardo Staglianò, Grazie. Ecco perché senza gli immigrati saremmo perduti.(Milano, Chiarelettere, 2010, pp.224. ISBN 978-88-61-90-086-8)Vladimiro Polchi, Blacks Out.(Roma-Bari, Laterza, 2010, pp.157. ISBN 978-88-420-9189-9)di Emanuele Monegato